Arginine methylation controls growth regulation by E2F-1 - Cho, E; Zheng, S; Munro, S; Liu, G; Carr, S; Moehlenbrink, J; Lu, Y; Stimson, L; Khan, O; Konietzny, R; McGouran, J; Coutts, A; et al. (2012)
E2F transcription factors are implicated in diverse cellular functions. The founding member, E2F-1, is endowed with contradictory activities, being able to promote cell-cycle progression and induce apoptosis. However, the mechanisms that underlie the opposing outcomes of E2F-1 activation remain largely unknown. We show here that E2F-1 is directly methylated by PRMT5 (protein arginine methyltransferase 5), and that arginine methylation is responsible for regulating its biochemical and functional properties, which impacts on E2F-1-dependent growth control. Thus, depleting PRMT5 causes increased E2F-1 protein levels, which coincides with decreased growth rate and associated apoptosis. Arginine methylation influences E2F-1 protein stability, and the enhanced transcription of a variety of downstream target genes reflects increased E2F-1 DNA-binding activity. Importantly, E2F-1 is methylated in tumour cells, and a reduced level of methylation is evident under DNA damage conditions that allow E2F-1 stabilization and give rise to apoptosis. Significantly, in a subgroup of colorectal cancer, high levels of PRMT5 frequently coincide with low levels of E2F-1 and reflect a poor clinical outcome. Our results establish that arginine methylation regulates the biological activity of E2F-1 activity, and raise the possibility that arginine methylation contributes to tumourigenesis by influencing the E2F pathway. © 2012 European Molecular Biology Organization | All Rights Reserved.